Development of perovskite and phase transition in lead cobalt niobate modified lead zirconate titanate system - Naratip Vittayakorn (2018)
Ferroelectric lead zirconate titanate-lead cobalt niobate ceramics with the formula (1 - x)Pb(Zr1/2Ti1/2)O3-xPb(Co1/3Nb2/3)O3where x = 0.0-0.5 were fabricated using a high temperature solid-state reaction method. The formation process, the structure and homogeneity of the obtained powders have been investigated by X-ray diffraction method as well as the simultaneous thermal analysis of both differential thermal analysis (DTA) and thermogravimetry analysis (TGA). It was observed that for the binary system (1 - x)Pb(Zr1/2Ti1/2)O3-xPb(Co1/3Nb2/3)O3, the change in the calcination temperature is approximately linear with respect to the PCoN content in the range x = 0.0-0.5. In addition, X-ray diffraction indicated a phase transformation from a tetragonal to a pseudo-cubic phase when the fraction of PCoN was increased. The dielectric permittivity is remarkably increased by increasing PCoN concentration. The maximum value of remnant polarization Pr(25.3 μC/cm2) was obtained for the 0.5PZT-0.5PCoN ceramic. © 2007 Elsevier B.V. All rights reserved.